Electrodeposited metal-organic framework films as self-assembled hierarchically superstructured supports for stable omniphobic surface coatings. Issue 1 (December 2018) - Sablowski, Jakob; Linnemann, Julia; Hempel, Simone; Hoffmann, Volker; Unz, Simon; Beckmann, Michael; Giebeler, Lars
Abstract Superhierarchically rough films are rapidly synthesised on metal substrates via electrochemically triggered self-assembly of meso/macroporous-structured metal-organic framework (MOF) crystals. These coatings are applied to immobilise a functional oil with low surface energy to provide stable coatings repellent to a wide range of hydrophobic as well as hydrophilic fluids. Such omniphobic surfaces are highly interesting for several applications such as anti-fouling, anti-icing, and dropwise condensation, and become easily scalable with the presented bottom-up fabrication approach. As investigated by environmental scanning electron microscopy (ESEM), the presented perfluorinated oil-infused Cu-BTC coating constitutes of a flat liquid-covered surface with protruding edges of octahedral superstructured MOF crystals. Water and non-polar diiodomethane droplets form considerably high contact angles and even low-surface-tension fluids, e.g. acetone, form droplets on the infused coating. The repellent properties towards the test fluids do not change upon extended water spraying in contrast to oil-infused porous copper oxide or native copper surfaces. It is discussed in detail, how the presented electrodeposited MOF films grow and provide a proficient surface morphology to stabilise the functional oil film due to hemiwicking.